2021
DOI: 10.1029/2020wr028117
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Indicators and Optimizing Decision Rules for Long‐Term Water Resources Planning

Abstract: Water planners must address these issues through improved water conservation, resources coordination, and capacity expansion projects. However, uncertainties arising from climate change, population growth, changing patterns of water demand and consumption, technological advancements, and regulatory reform continue to complicate water resources planning problems (Brown et al., 2015;Wilby & Dessai, 2010). Previous research has sought to overcome these issues by identifying long-term and short-term water system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
(196 reference statements)
0
5
0
Order By: Relevance
“…distributions of SF MD and RCSL. This enables robust decision making under various types of uncertainties (He et al, 2021;Moallemi et al, 2021;Murgatroyd & Hall, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…distributions of SF MD and RCSL. This enables robust decision making under various types of uncertainties (He et al, 2021;Moallemi et al, 2021;Murgatroyd & Hall, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with existing point estimate using deterministic approaches, our probabilistic framework can provide the full distributions of SF MD and RCSL. This enables robust decision making under various types of uncertainties (He et al., 2021; Moallemi et al., 2021; Murgatroyd & Hall, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the selection of evaluation indexes is carried out through two aspects. A large portion of the literature on water resources carrying capacity evaluation was consulted, and the indicators that were used more frequently were selected [30][31][32]. For the regional characteristics and water resources conditions and status quo of Zhangye City, and following the principles of scientificity, representativeness, reliability, and accessibility [33], the corresponding 12 indicators were selected.…”
Section: Construction Of Water Resources Carrying Capacity Index Systemmentioning
confidence: 99%
“…The outcomes of these actions can inform infrastructure investment and sequence mitigative actions in planning for future extreme climate events (Haasnoot et al., 2019; Kwakkel et al., 2015). More recently, the DAPP framework has been extended to water supply policy pathways management and investment pathways where dynamic risk‐of‐failure (ROF) focused policies are identified that use state‐aware action triggers for short‐term drought mitigation (Gold et al., 2019; Palmer & Characklis, 2009; Zeff et al., 2016) and long‐term infrastructure investments (Gorelick et al., 2022; Hyun et al., 2021; Murgatroyd & Hall, 2021; Trindade et al., 2019).…”
Section: Introductionmentioning
confidence: 99%